Deteksi Molekuler Tilapia Lake Virus (TiLV) pada Ikan Nila (Oreochromis niloticus) di Provinsi Kalimantan Timur, Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
Tilapia Lake Virus (TiLV) is an RNA pathogen that causes high mortality rates in tilapia (Oreochromis niloticus), posing a major threat to global aquaculture. This study aimed to detect the presence of TiLV in tilapia populations in East Kalimantan Province, Indonesia, using the Polymerase Chain Reaction (PCR) method. A total of 60 tilapia samples were collected from three main aquaculture areas: Kutai Kartanegara, Samarinda, and Penajam Paser Utara. Molecular analysis revealed that one sample from Penajam Paser Utara was positive for TiLV, with an overall prevalence of 5%, while all samples from other sites tested negative. This finding indicates that TiLV has been molecularly detected in East Kalimantan, albeit at a low prevalence. The overall prevalence of TiLV infection in East Kalimantan was 1.67%. The results provide important baseline data for strengthening disease surveillance, biosecurity implementation, and the development of preventive strategies in tilapia aquaculture systems in Indonesia.